EFEKTIVITAS PENGGUNAAN CHROMEBOOK DALAM MENDUKUNG PEMBELAJARAN DIGITAL MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA BAITUL QUR’AN CENDEKIA - Sufiana, Isti; Abbas, Ngatmin; Fathurohman, Alim; Pangesti, Yanuar Bagas; Robbani, Ibrahim Jundi (Jurnal Manajemen Pendidikan, 2025)
This study aims to investigate the effectiveness of using Chromebooks in supporting digital learning for the Islamic Religious Education (PAI) subject at SMP Baitul Qur’an Cendekia. The research focuses on five key aspects: students’ habits and readiness in using Chromebooks, their perceptions of ease and understanding of PAI materials, the level of creativity and engagement in digital-based learning, technical challenges encountered, and the relevance of Chromebook integration with the goals of Islamic education in the digital era. This study employed a quantitative approach using survey and literature study methods. Data were collected through questionnaires administered to 17 students and in-depth interviews with a PAI teacher. The data were analyzed using descriptive quantitative and qualitative methods to gain a comprehensive understanding of Chromebook usage effectiveness in the learning process. The findings show that most students feel accustomed to and comfortable using Chromebooks in PAI learning. The device is perceived to facilitate understanding of the material, increase learning motivation, and enhance student creativity in completing project-based assignments such as Islamic videos and digital content design. However, technical issues and limitations in conveying spiritual values through digital media were also identified.